Epidermal Growth Factor Receptor Regulates MT1-MMP and MMP-2 Synthesis in SiHa Cells via Both PI3-K/AKT and MAPK/ERK Pathways. Issue 6 (1st July 2009) - Zhang, Zongfeng; Song, Tiefang; Jin, Yinglan; Pan, Jiaqi; Zhang, Liying; Wang, Lingdi; Li, Peiling
Abstract : Matrix metalloproteinase 2 (MMP-2) and membrane type 1 matrix metalloproteinase (MT1-MMP) have been identified as important participants in tumor invasion, metastasis, and angiogenesis. Membrane type 1 matrix metalloproteinase has also been recognized as a major activator of MMP-2. The purpose of this study was to investigate epidermal growth factor (EGF) mediating signal pathways in the regulation of MMP-2 and MT1-MMP in SiHa cells, a cervical cancer cell line. We showed here that EGF induced the expression of MT1-MMP and inhibited the expression of MMP-2 at both the mRNA and protein levels. Membrane type 1 matrix metalloproteinase induction was blocked by mitogen-activated protein kinase or extracellular signal-regulated kinase inhibitors PD98059 and U0126 but not by phosphatidylinositol-3 kinase (PI3-K) inhibitors LY294002 and wortmannin. Interestingly, the mitogen-activated protein kinase or extracellular signal-regulated kinase inhibitors PD98059 and U0126 actually increased MMP-2 mRNA and protein synthesis, whereas the PI3-K inhibitors LY294002 and wortmannin further suppressed the expression of MMP-2. Our results suggest that EGF receptor up-regulated the expression of MT1-MMP and down-regulated the synthesis of MMP-2 through the mitogen-activated protein kinase/extracellular signal-regulated kinase pathway while concomitantly transmitting a mild positive regulatory signal to the expression of MMP-2 via the PI3-K/AKT pathway in SiHa cells. Furthermore, we found that EGF elevated the activity of MMP-2 in culture media.